Assessment of environmental quality, degree of optimism, and the assignment of responsibility regarding the state of the environment in Latin America - Páramo, Pablo (2015)
This study explores the assessments made by the inhabitants of eight Latin American countries regarding the current state of the environment, at a local, national and global scale, and how it is perceived looking ahead to the future. It also examines the assignment of responsibility in the future management of the environment. A total of 944 people took part in the study from the eight participating countries, men and women over the age of 18 with different levels of education. The study uses the Environmental Futures Scale to which two relevant items have been added to assess the environment in the region, as well as the Assignment of Environmental Responsibility Scale. The results show differences between the countries, although in general they are pessimistic regarding the current and future state of the environment at the local, national and global level, with the exception of Brazil. In general, and with the exception of Brazil, in the countries surveyed, people assign a high level of responsibility to external social agents at the different levels, increasing their judgement of external responsibility at the national and global levels of analysis. The implications of these findings for environmental policy and education in the countries of this region are also discussed.